Self Portrait as a Semiopext(e) Foreign Agent - Messham-Muir, Kit; Gladwell, S.; Patton, P.; Thwaites, D. (Sherman Contemporary Art Foundation, 2015)
’Self Portrait as a Semiopext(e) Foreign Agent’ is an artwork book created by artist Shaun Gladwell in collaboration with Kit Messham-Muir, Denise Thwaites and Paul Patton. The artwork book is an original theoretical text presented in the form of a faux Semiopext(e) Foreign Agent theory book. The title on the book’s cover is ’Shaun Gladwell: Patafunctions’. This work was commissioned by the Sherman Contemporary Art Foundation, Sydney, as part of Shaun Gladwell’s exhibition, The Lacrima Chair, exhibited at the SCAF gallery in Goodhope Street, Paddington NSW, Australia, 6 March - 25 April 2015.